Effects of physical training on depression and related quality of life in pre-frail and frail older adults: a systematic review and meta-analysis - Wei-Han Weng; Yin-Hsiang Wang; Nai-Chen Yeh; Yea-Ru Yang; Ray-Yau Wang (Elsevier, 2024)
Objectives: To investigate the effects of physical training on depression and related quality of life in pre-frail and frail individuals. Design: A systematic review and meta-analysis. Participants: Pre-frail and frail older adults. Methods: Five electronic databases, including PubMed, Cochrane, Medline, CINAHL, and Wiley were searched through December 2023. Randomized controlled trials (RCT) comparing physical training with usual care, health education, or light-intensity exercise were included. Outcomes included depression and depression-related quality of life. The quality of the included studies was assessed using Physiotherapy Evidence Database (PEDro) score, and the Cochrane Risk of Bias Tool was used to assess the risk of bias. Meta-analysis was performed using the RevMan5.4. The certainty of the evidence was evaluated by The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Results: Ten articles with 589 participants met the inclusion criteria and were included. The pooled analysis indicated that depression (SMD = −0.55, 95%CI = −0.92, −0.17, p = 0.004) and mental health status in life (SMD = 1.05, 95%CI = 0.59, 1.50, p < 0.00001) improved significantly in the experimental group. The results of subgroup analysis revealed that the beneficial effects of physical training were significant only in frail older adults but not in pre-frail older adults. Conclusion: This meta-analysis showed that the positive effects of physical training on depression and related quality of life were evident for people with frailty. However, no positive results were observed in pre-frail older adults, indicating the need for further investigation in this subgroup.